2018
DOI: 10.22159/ajpcr.2018.v11i6.22499
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Pattern of Self-Medication Among Students for Dysmenorrhea

Abstract: Objectives: The objectives of this study were to assess the pattern of self-medication for dysmenorrhea among students and compare it between medical and non-medical students.Methods: The observational study was conducted from May to August 2014. After obtaining the Institutional Ethics Committee approval and written informed consent from all students with dysmenorrhea aged between 18 and 25 years were included in the study. Demographic details such as age and duration of dysmenorrhea per cycle were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
4
1
0
Order By: Relevance
“…In the present study, the mean age of students was 20.88±1.51years which was more or less similar to Anand S et al 8 195 (72.5%) participants had regular menstrual cycle which was similar to the study done in India by Jayanthi B et al 9 Among 269 participants who experienced dysmenorrhea, 191 (71%) of the participants reported 4-5 days of menstrual cycle and 189 (70%) reported pain for first 2 days of menstrual flow which was similar to Banikarim C et al and Fatima A et al 10,11 Assessment of pain intensity and duration revealed that female undergraduates experience mild, moderate, severe, very severe and worst pain during menstruation which was similarly explained in the study done in China by Chen 12 and Nigeria by Emmanuel et al 13 Most females in this survey experienced mild or moderate pain in the age group 21-25 years. The differences in the pain severity may be related to individual differences in pain perception and variability in pain threshold.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, the mean age of students was 20.88±1.51years which was more or less similar to Anand S et al 8 195 (72.5%) participants had regular menstrual cycle which was similar to the study done in India by Jayanthi B et al 9 Among 269 participants who experienced dysmenorrhea, 191 (71%) of the participants reported 4-5 days of menstrual cycle and 189 (70%) reported pain for first 2 days of menstrual flow which was similar to Banikarim C et al and Fatima A et al 10,11 Assessment of pain intensity and duration revealed that female undergraduates experience mild, moderate, severe, very severe and worst pain during menstruation which was similarly explained in the study done in China by Chen 12 and Nigeria by Emmanuel et al 13 Most females in this survey experienced mild or moderate pain in the age group 21-25 years. The differences in the pain severity may be related to individual differences in pain perception and variability in pain threshold.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the mean age of students was 20.88±1.51years which was more or less similar to Anand S et al 8 195 (72.5%) participants had regular menstrual cycle which was similar to the study done in India by Jayanthi B et al 9 Among 269 participants who experienced dysmenorrhea, 191 (71%) of the participants reported 4-5 days of menstrual cycle and 189 (70%) reported pain for first 2 days of menstrual flow which was similar to Banikarim C et al and Fatima A et al 10 , 11 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Respondent satisfaction in the reliability of self-medicated service products also shows good satisfaction. The reliability in reducing minor pain symptoms is in accordance with the obvious use and way of using the drug [21].…”
Section: Customer Satisfactionmentioning
confidence: 81%